2019
DOI: 10.1093/pm/pnz248
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Radiofrequency Ablation of Medial Branch Nerves for Chronic Lumbar Facet Joint Syndrome in Patients Selected by Guideline-Concordant Dual Comparative Medial Branch Blocks

Abstract: Objectives Although the effectiveness of lumbar medial branch radiofrequency ablation (RFA) for the treatment of zygapophyseal joint (z-joint)–mediated low back pain has been characterized, few studies have described outcomes in patients selected using a guideline-concordant paradigm of ≥80% pain relief with dual comparative medial branch blocks (MBBs). We investigated long-term treatment outcomes of patients selected according to this paradigm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 28 publications
0
25
1
Order By: Relevance
“…More recently, a retrospective review performed in 111 patients who responded with ≥80% concordant pain relief after comparative LA MBB found that older age and a smaller Cobb angle were associated with > 50% pain reduction 6 months after RFA. 56 Finally, in a large, prospective study that sought to determine factors associated with interventional treatment outcomes in 318 patients with LBP (63 with suspected facetogenic pain), Cohen et al found that 51.1% of individual with 0 Waddell signs, 34.1% with one or two signs, 26.1% with three or four signs and only 16.7% of people with five of five Waddell signs experienced a positive treatment outcome. Other variables associated with treatment success included older age, shorter duration of pain, lower baseline pain scores and better function, absence of secondary gain and not having concomitant pain and psychiatric comorbidities.…”
Section: Question 1: Can History and Physical Examination Be Used To mentioning
confidence: 99%
“…More recently, a retrospective review performed in 111 patients who responded with ≥80% concordant pain relief after comparative LA MBB found that older age and a smaller Cobb angle were associated with > 50% pain reduction 6 months after RFA. 56 Finally, in a large, prospective study that sought to determine factors associated with interventional treatment outcomes in 318 patients with LBP (63 with suspected facetogenic pain), Cohen et al found that 51.1% of individual with 0 Waddell signs, 34.1% with one or two signs, 26.1% with three or four signs and only 16.7% of people with five of five Waddell signs experienced a positive treatment outcome. Other variables associated with treatment success included older age, shorter duration of pain, lower baseline pain scores and better function, absence of secondary gain and not having concomitant pain and psychiatric comorbidities.…”
Section: Question 1: Can History and Physical Examination Be Used To mentioning
confidence: 99%
“…43 Hence, the literature illustrates that there are no pathognomonic signs with both clinical history and physical examination to reliably diagnose patients with facet-mediated pain or predict the success of LRFN. [43][44][45] Moreover, both MRI and CT scans have no specific findings that help diagnose lumbar facet mediated pathology as the exclusive source of pain. 46,47 As such, the present standard in the diagnosis of lumbar facet mediated pain is diagnostic facet blocks, including both the use of intra-articular facet joint injections and medial branch nerve blocks.…”
Section: Current Available Evidence Of Lumbar Medial Branch Radiofrequency Neurotomymentioning
confidence: 99%
“…LRFN has been studied extensively with consensus guidelines indicating moderate to strong evidence. [43][44][45] The efficacy of the lumbar medial branch RFN has been described in observational and RCT. Out of the six RCTs, three contained technical flaws in both patient selection and procedural technique, which yielded less reliable and therefore, non-generalizable findings.…”
Section: Current Available Evidence Of Lumbar Medial Branch Radiofrequency Neurotomymentioning
confidence: 99%
“…13 Although we observed positive clinical outcomes in a substantial proportion of patients after L-SIJRFA, the present results are inferior to RFA for the treatment of lumbar and cervical facet-mediated pain. [20][21][22][23][24] Selection criteria may be an explanation for outcome discrepancies, despite likely complete ablation of neural tissue. Participants in the current study were selected based on 50% or more pain relief after dual blocks (intraarticular and LBB or LBB and LBB).…”
Section: Discussionmentioning
confidence: 99%